Accelerated high-frequency repetitive transcranial magnetic stimulation enhances motor activity in rats. (7th April 2017) - El Arfani, Anissa; Parthoens, Joke; Demuyser, Thomas; Servaes, Stijn; De Coninck, Mattias; De Deyn, Peter Paul; Van Dam, Debby; Wyckhuys, Tine; Baeken, Chris; Smolders, Ilse; Staelens, Steven
Highlights: Accelerated HF-rTMS was robustly performed on small animals. Accelerated HF-rTMS enhances rat motor activity. Accelerated HF-rTMS reduces the total striatal 5-hydroxyindolacetic acid levels. Abstract: High-frequency repetitive transcranial magnetic stimulation (HF-rTMS) is currently accepted as an evidence-based treatment option for treatment-resistant depression (TRD). Additionally, HF-rTMS showed beneficial effects on psychomotor retardation in patients. The classical HF-rTMS paradigms however are unlikely to replace electroconvulsive therapy, a more potent alternative for TRD albeit with important side-effects. Therefore, recent studies have investigated 'accelerated' HF-rTMS protocols demonstrating promising clinical responses in patients with TRD. Since the neuronal effects of accelerated HF-rTMS are underinvestigated, we evaluate here the possible metabolic and neurochemical effects of this treatment alternative. More specifically, we measured the effect on brain glucose metabolism and monoamines/metabolites, as well as on the spontaneous motor activity in rats. We found that brain glucose metabolism and monoamines remained generally unaffected after accelerated HF-rTMS, with the exception of reduced total striatal 5-hydroxyindolacetic acid (a metabolite of serotonin) levels. Interestingly, when compared to sham stimulation, the velocity, the total distance traveled as well as the percentage of movement, as measured by the open-field test, were significantly enhanced after accelerated HF-rTMS showing an increased motor activity. Our current results indicate that the accelerated HF-rTMS-induced increase in motor activity in rats, may be related to the striatal neurochemical effect.